The experiences of Arab teachers in Jewish schools in Israel. (March 2019) - Saada, Najwan; Gross, Zehavit
Abstract: In this multiple case study, we explore the experiences of ten Palestinian Israeli and Arab teachers who teach Arabic culture and language in Jewish schools in Israel. Two themes are revealed in this inquiry. The first theme highlights the ambivalent message of teaching Arabic as the language of the 'enemy' and as a medium for peace building. The second theme clarifies how minority teachers navigate, by applying a narrative model, the tension between their national (Palestinian) and professional identities. The implications for teaching and teacher education in conflict-ridden societies are also discussed. Highlights: Arab teachers: agents of the Arab minority challenging student negative stereotypes. They can counter personal bias to achieve better recognition of their Arab identity. This personal interaction may still not counter student essentialized perceptions. Individual interactions may not extend to the collective Palestinian, Arab groups. Narrative model: a pedagogic tool to negotiate professional/personal identities.